Analisis Pengaruh Kualitas Produk, Kualitas Pelayanan,Dan Kepuasan Konsumen Terhadap Loyalitas KonsumenSerabi Notosuman Di Surakarta - Putranti, Reisa Indra, Drs. M.Nasir, MM (2017)
The purpose of this thesis intends to determine the effect of product quality on customer loyalty, service quality on customer loyalty and customer satisfaction on loyalty of Serabi Notosuman's customer in Surakarta. Population in this research is Serabi Notosuman's customer in Surakarta. Samples are taken with 40 respondents using non random sampling techniques that not all of members of populations were given the opportunity to be selected into the sample. To achieve the purpose, this research uses an analytical tool such as analysis of the validity, reliability, tests of hypotheses and assumptions of classical test conducted by using SPSS for Windows 17. Based on the results obtained regression equation as follows: Y = 2,045 + 0,277X1+0,215X2+0,217X3. Based on the analysis, indicators in this thesis are valid and the reliable variables. On the classic assumption test, free multikolinearitas regresssion model, doesn't occur heteroskedastisitas, and as normal distribution. Individually sequence of each of the most influential variable is the variable quality of the product with a regression coefficient is 0,277 then the variable consumer satisfaction with regression coefficient is 0,217 while the variable quality of service with a regression coefficient is 0,215.